1981
DOI: 10.1128/aem.41.3.610-617.1981
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transformation of β -Ionone and β -Methylionone

Abstract: Aspergillus niger JTS 191 was selected from many microorganisms tested as capable of converting ionones to other compounds having aromas. The individual transformation products from ,B-ionone were isolated and identifled by comparison with synthetically derived compounds. The major products were (R)-4hydroxy-f8-ionone and (S)-2-hydroxy-fl-ionone. 2-Oxo-, 4-oxo-, 3,4-dehydro-, 2,3dehydro-4-oxo-, 3,4-dehydro-2-oxo-, (S)-2-acetoxy-, (R)-4-acetoxy-, and 5,6epoxy-,8-ionone and 4-(2,3,6-trimethylphenyl)-but-3-en-2-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Allylic acetate 3 has previously been described as the product of microbial oxidation, the electrochemical oxidation of β‐ionone, and the lipase‐catalyzed trans ‐esterification of the corresponding alcohol that was obtained by the microbial oxidation of β‐ionone …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Allylic acetate 3 has previously been described as the product of microbial oxidation, the electrochemical oxidation of β‐ionone, and the lipase‐catalyzed trans ‐esterification of the corresponding alcohol that was obtained by the microbial oxidation of β‐ionone …”
Section: Resultsmentioning
confidence: 99%
“…Ketone 4 , which is a natural product with a pleasant floral scent, was previously synthesized by the palladium‐catalyzed arylation of 2,3,6‐trimethylbromobenzene with 3‐butene‐2‐one . A few examples in the literature have shown that ketone 4 can also be formed directly from ionones . The microbial oxidation of β‐ionone gave compound 4 in minor amounts, along with acetate 3 (in 1–2 % yield each) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Ionone stripping and chemical products synthesis were calculated using the above limiting mass transfer rate model (eqs [4][5][6]. Residual -ionone available for biotransformation was then deduced by difference between total precursor consumption and the sum of the amounts stripped and chemically degraded.…”
Section: Estimation Of the Gas-aqueous Phase Volumetric Mass Transfermentioning
confidence: 99%
“…The extract was analyzed by gas chromatography. 2) The substrate peak disappeared after 48hr and seven peaks appeared concomitantly with the decrease in the substrate (Fig. 1).…”
mentioning
confidence: 91%